Hypertension in the Kutai Community in Penyinggahan Village, West Kutai Regency. Is There a Relationship with Physical Activity? A Cross-Sectional Study - Wahyudi, Wahyudi; Pakki, Irfansyah Baharuddin; Siswanto, Siswanto; Arfandi, Muh. Amri (Universitas Mulawarman, 2025)
Hypertension is a major health problem in Indonesia, with a prevalence rate of 39.3% in East Kalimantan, including in West Kutai Regency. This study aims to analyze the relationship between consumption of high-risk foods and beverages and physical activity with the incidence of hypertension among the Kutai people in the working area of the Penyinggahan Health Center. A cross-sectional study was conducted in 2023 with a sample of 140 respondents aged 30–64 years selected by purposive sampling. Data were collected using FFQ and IPAQ questionnaires and analyzed using univariate, bivariate (Chi-Square and Fisher's Exact Test), and multivariate (Logistic Regression) methods. The results showed that 51.4% of respondents suffered from hypertension, with significant associations found with high-risk BMI (p=0.000; OR=3.699), moderate-to-vigorous physical activity (p<0.05), and consumption of fat, oil, salt, and sugar (p<0.05). No significant relationships were found with protein, fiber, potassium, fruits, vegetables, age, gender, or ethnicity. In conclusion, high-risk BMI, inadequate physical activity, and dietary patterns low in protein, fiber, and potassium are dominant risk factors for hypertension among the Kutai people.